Algorithm of reactive power dispatching “per generator” realization on TPP Nikola Tesla A - Pavlović, Jelena; Radojičić, Bojan; Stančić, Lazar; Dragosavac, Jasna; Dobričić, Sava; Janda, Žarko (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
The algorithm of reactive power dispatching “per generator” realization is presented in the paper. Dispatching “per generator” and “per grid” are two modes of reactive power dispatching used by coordinated reactive power and voltage regulator (GRRS). Reactive power dispatching “per generator” ensures equal heating of the generators, while dispatching “per grid” ensures maximal reactive power reserve when generated reactive power either increases, or decreases. Reactive power dispatching “per generator” is more complex for realization because the dispatching criterion may have wider generator’s reactive power operation area than the working capability curve. In these cases, the additional limiting of the generator reactive power is necessary, while other generators take over the remaining reactive power, still considering the reactive power dispatching criteria “per generator” and the limits of the remaining generators. Both reactive power dispatching modes are presented in two examples, while operating near and far from the limit area. Eventually, as the verification of the algorithm and its realization, the operating results of GRRS while dispatching “per generator” is active, are presented.
Keywords: joint control, reactive power, synchronous generator, reactive reserve.